2022
DOI: 10.52965/001c.40321
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Mental Health and Trauma in Interstitial Cystitis

Abstract: This review aims to assess the relationship between interstitial cystitis (IC) and significant traumatic events or PTSD. It was shown that there is a strong correlation between past trauma and the development of interstitial cystitis, as well as a much higher incidence of PTSD in patients diagnosed with IC. It was also established that for individuals with early traumatic experiences, the more likely the development of IC later in life, and with more severe symptoms and adverse effects on quality of life. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Predisposing risk factors that can increase susceptibility to IC include genetic vulnerability ( 12 ), family ( 104 , 119 ) medical ( 120 ) and mental health history ( 121 ), personality traits ( 122 ), ELA and RLA ( 14 ), age ( 119 ). and gender ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing risk factors that can increase susceptibility to IC include genetic vulnerability ( 12 ), family ( 104 , 119 ) medical ( 120 ) and mental health history ( 121 ), personality traits ( 122 ), ELA and RLA ( 14 ), age ( 119 ). and gender ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, chronic stress has been identified as a key risk factor in developing IC/BPS in otherwise healthy patients ( Birder, 2019 ), and a number of studies have reported higher incidences of early life stress in IC/BPS patients than healthy controls ( Fuentes and Christianson, 2018a ). The precise mechanisms regulating stress induced IC/BPS are unclear, however, evidence is accumulating that the functional impacts of stress on bladder function and the perception of painful stimuli are likely mediated by long-term perturbations of the HPA axis and the sympathetic-adrenal medulla pathway ( Figure 1 ) ( de Groat et al, 2015 ; Fuentes and Christianson, 2018b ; Bendrick et al, 2022 ). The downstream effectors of these pathways, including CRF, cortisol, and noradrenaline are well known regulators of urinary function and thought to be crucial in regulating centrally mediated changes that induce IC/BPS symptoms ( Ulrich-Lai and Herman, 2009 ; Pierce and Christianson, 2015 ).…”
Section: Mechanisms Underlying Ic/bpsmentioning
confidence: 99%